REVIEW OF SARS-CORONAVIRUS-2 REPERCUSSIONS ON THYROID GLAND IN THE CONTEXT OF HYPERTHYROIDISM - SINGH, SHUBHAM; MONIKA; MAZUMDER, RUPA; MAZUMDER, AVIJIT (International Journal of Applied Pharmaceutics, 2023)
The thyroid gland may generate, store, and release hormones (such as Triiodothyronine and Thyroxin also called T3 and T4 hormones respectively) into the bloodstream and let them go to the body's cells. Every enzymatic process in the production and secretion of thyroid hormones is controlled by Thyroid stimulating hormone (TSH). All people worldwide are susceptible to thyroid disease, which is often accompanied by hyperthyroidism and hypothyroidism. The thyroid's structural proximity to the upper airways, a main route for coronavirus entry, holds up the idea that the thyroid gland might be a target for Covid-19 or SARS-CoronaVirus-2. When the thyroid gland makes and secretes too much thyroid hormone, it is referred to as hyperthyroidism and if the patients do not take any precautions, hyperthyroidism may lead to cardiac hypertrophy. The Covid-19 epidemic had a substantial influence on our daily lives and has unexpectedly changed the way of medical research. This review aimed to discuss the effects of SARS-CoronaVirus-2 on the Thyroid Gland in the Context of Hyperthyroidism and related causing diseases, highlighting the common causing diseases of hyperthyroidism along with their treatments. We also highlight the impact of SARS-CoronaVirus-2 and its mRNA immunization. So that future studies should focus on the number of important advances and improved drug management in the treatment of Thyroid relating diseases, which may or may not be triggered by the coronavirus and its immunization.